Cathepsin K activity controls cardiotoxin‐induced skeletal muscle repair in mice. Issue 1 (23rd October 2017) - Ogasawara, Shinyu; Cheng, Xian Wu; Inoue, Aiko; Hu, Lina; Piao, Limei; Yu, Chenglin; Goto, Hiroki; Xu, Wenhu; Zhao, Guangxian; Lei, Yanna; Yang, Guang; Kimura, Kaoru; et al.
Abstract: Background: Cathepsin K (CatK) is a widely expressed cysteine protease that has gained attention because of its enzymatic and non‐enzymatic functions in signalling. Here, we examined whether CatK‐deficiency (CatK −/− ) would mitigate injury‐related skeletal muscle remodelling and fibrosis in mice, with a special focus on inflammation and muscle cell apoptosis. Methods: Cardiotoxin (CTX, 20 μM/200 μL) was injected into the left gastrocnemius muscle of male wild‐type (CatK +/+ ) and CatK −/− mice, and the mice were processed for morphological and biochemical studies. Results: On post‐injection Day 14, CatK deletion ameliorated muscle interstitial fibrosis and remodelling and performance. At an early time point (Day 3), CatK −/− reduced the lesion macrophage and leucocyte contents and cell apoptosis, the mRNA levels of monocyte chemoattractant protein‐1, toll‐like receptor‐2 and toll‐like receptor‐4, and the gelatinolytic activity related to matrix metalloproteinase‐2/‐9. CatK deletion also restored the protein levels of caspase‐3 and cleaved caspase‐8 and the ratio of the BAX to the Bcl‐2. Moreover, CatK deficiency protected muscle fibre laminin and desmin disorder in response to CTX injury. These beneficial muscle effects were mimicked by CatK‐specific inhibitor treatment. In vitro experiments demonstrated that pharmacological CatK inhibition reduced the apoptosis of C2C12 mouse myoblasts and the levels of BAX and caspase‐3 proteins induced by CTX. Conclusions: These results demonstrate that CatK plays an essential role in skeletal muscle loss and fibrosis in response to CTX injury, possibly via a reduction of inflammation and cell apoptosis, suggesting a novel therapeutic strategy for the control of skeletal muscle diseases by regulating CatK activity.